The Role of S1P and the Related Signaling Pathway in the Development of Tissue Fibrosis - Wang, Erjin; He, Xingxuan; Zeng, Ming (Frontiers in Pharmacology, 2019)
Tissue fibrosis, including pulmonary fibrosis, hepatic fibrosis, and cardiac fibrosis, is an important stage in the development of many diseases. It can lead to structural damage and dysfunction and even severe carcinogenesis or death. There is currently no effective method for the treatment of fibrosis. At present, the molecular mechanism of tissue fibrosis has not yet been fully elucidated, but many studies have demonstrated that it is involved in conveying the complex messages between fibroblasts and various cytokines. S1P and its signaling pathways are important intracellular metabolic pathways involved in many life activities, including cell proliferation, differentiation, apoptosis, and cellular signal transduction. Increasing evidence suggests that S1P and its signaling pathways play an important role in the development of tissue fibrosis; however, the mechanisms of these effects have not yet been fully elucidated, and even the role of S1P and its signaling pathways are still controversial. This article focuses on the role of S1P and its signaling pathways in the fibrosis of lung, liver, heart, and other tissues, with emphasis on its application in clinical treatment of fibrosis diseases.